IMF Survey, Volume 37, Issue 09. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2008)
Antoinette Sayeh interview, IMF clarifies surveillance process, Georgia loan, Olivier Blanchard interview, Africa's financial sector, EMU slowdown, EU transfers, sovereign wealth fund principles, United Kingdom outlook, Uruguay's financial issues, Saudi Arabia's oil bonanza, news briefs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet